Comparison relative of abundance of Capoeta capoeta gracilis in five streams of Gorganroud River Basin, Golestan Province, Northern Iran - Ranjbar, Khadijeh Shamekhi; Patimar, Rahman; Ghorbani, Rasoul; Kordjazi, Zia (Journal of Research in Biology, 2012)
In this study 1705 individuals have sampled during spawning season in five streams of Gorganroud basin and investigated the lengths and relative abundance. The length varied from 4.1-23.2 cm.there were significant difference in length frequencies between male and female in each streams and length classes. Sex ratio was 1:1.78. Male dominance was observed in all population. Sixteen length classes were present. Maximum frequency was length class length 8.9-10.1 cm for males and 7.7-8.9 cm for females. Males were more frequent in medium size. Females were in varied size.